The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/1873-3468.13282
|View full text |Cite
|
Sign up to set email alerts
|

miR‐342‐3p promotes osteogenic differentiation via targeting ATF3

Abstract: Through their multiple targets, microRNAs (miRNAs) are involved in numerous physiological and pathological processes. In this study, miR‐342‐3p was found to be deregulated with ossification of ligament or osteoporosis. We demonstrate that silencing miR‐342‐3p impairs osteoblast activity and matrix mineralization, while over expression of miR‐342‐3p promotes osteoblast differentiation significantly. Moreover, miR‐342‐3p directly targets activating transcription factor 3 (ATF3), which inhibits transcription of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…In the current study, we suggest that a miRNA is an upstream regulator of ATF3. Indeed, an alternate miRNA, miR-342-3p , targets ATF3 to promote osteogenic differentiation of human mesenchymal stem cells, 67 which implicates the existence of a diverse miRNA-ATF3 network. In this study, we did not address which upstream signals affect the decrease in the expression of miR-27a-3p .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we suggest that a miRNA is an upstream regulator of ATF3. Indeed, an alternate miRNA, miR-342-3p , targets ATF3 to promote osteogenic differentiation of human mesenchymal stem cells, 67 which implicates the existence of a diverse miRNA-ATF3 network. In this study, we did not address which upstream signals affect the decrease in the expression of miR-27a-3p .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that EVL contained a CpG island in the promoter region, and the CpG island aberrant methylation inhibited miR-342 expression in human colorectal cancer, which was a transcription product of EVL intron [42]. Another article confirmed the effect of miR-342-3p in osteogenic differentiation and explored the regulation mechanism between miR-342-3p and DNA methylation of its hosting gene EVL [37]. They found hypomethylation in the promoter of EVL promoted the miR-342-3p expression in osteogenic differentiation, Li et al [35] miRNA miR-29b MiR-29b targeted DNMT1 and led to the methylation modification in the Notch1 promoter, which affected the Notch signaling pathway and regulated the osteogenic differentiation in BMSCs.…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
“…Han et al [37] lncRNA H19 H19 has a strong osteogenic effect via the NOTCH1 pathway, and hypomethylation in the H19 promoter was associated with the high expression of H19.…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
“…2018), miR-342-3p (Y. Han et al, 2018), miR-451a (Karvande et al, 2018), and miR-874 (Lin et al, 2018). In addition, it has recently been reported that miR-21 and miR-218 play a physiological role in osteocytes, which are differentiated OBs embedded in the bone matrix (Davis et al, 2017).…”
Section: Function Of Mirnas In Bone Physiologymentioning
confidence: 99%